PREPARATION OF JUNIPERUS EXTRACT AND DETECTION OF ITS ANTIMICROBIAL AND ANTIOXIDANT ACTIVITY - &et al., Maeh (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to produce silver nanoparticles by fruits extract of Juniperus phoenicea and comparison between the ethanolic extract and nano extract through the antioxidant, antibacterial, anti-parasite and cytotoxicity against prostate cancer. The synthesis of silver nanoparticles was shown by many characterizing techniques: UV, FTIR, XRD and SEM. Nano extract exhibited a higher antibacterial, antioxidant, antiparasite compared to ethanolic extract and higher cytotoxicity activity. The nano extract exhibited higher antibacterial activity compared with antibiotics. Finally, we study the toxicity of J. phoenicea by Inhibition of RBC hemolysis by H2O2, the results exhibited the highest inhibition activity of J. phoenicea against H2O2. The nanoextract of J. phoenicea can be used effectively in the production of potential antioxidant, antiparasite antimicrobial and anticancer.